Looking into New Sources of Bioactives: Seasonal Variation in Bioactive Compounds and Dietary Fiber of Agave Bagasse from Mezcal Production - Jimena Álvarez-Chávez; Elisa Dufoo-Hurtado; Liliana Santos-Zea; Aurea K. Ramírez-Jiménez (Foods)
The production of mezcal from agave is one of the main beverage industries worldwide, generating large amounts of waste, such as agave bagasse. Improper management of this waste often causes environmental contamination. Some studies have begun to demonstrate that agave bagasse has the potential to be recycled as a source of functional ingredients due to its dietary fiber and bioactive compound content. However, the greatest disadvantage of using these wastes is the significant variation in compound content and bioactivity in response to seasonal climatic variations. This study aimed to analyze the chemical and bioactive content of agave bagasse from three mezcal factories in Mexico. We conducted proximate composition analysis, phenolic compound measurement, dietary fiber assessment, antioxidant capacity evaluation, and structural analysis using FTIR- Fourier Transform Infrared Spectroscopy. The study found significantly higher ash content (17.75%), carbohydrates (86.71%), and soluble fiber (30.91%) in the spring compared to other seasons. The summer showed a higher lipid content (10.25%), while the highest concentration of sugars (47.77%) was observed during the winter. The highest antioxidant capacity (106.15 mM eq Trolox/mg) was recorded in autumn. The FTIR analysis revealed that the greatest abundance of bioactive compounds was observed in the spring and summer, while structural carbohydrates were more prominent in autumn and winter. This study is the first to thoroughly analyze the seasonal variation in phytochemicals and macromolecules in agave residues, crucial for exploring new ingredient sources to expand our food supply and recycling agri-food wastes.